The characterization of glass fibre reinforced unsaturated polyester filled with P84 Polyimide / multi-wall carbon nanotubes (mwcnt) hybrid composites / Nik Noor Idayu Nik Ibrahim - Nik Ibrahim, Nik Noor Idayu (Institute of Graduate Studies, 2017)
This study was carried out with an aim to improve the strength and thermal stability of the glass fibre reinforced unsaturated polyester composites by incorporating the P84 Polyimide powder and Multi-wall Carbon Nanotubes (MWCNT) as filler. Research methodology for this study was divided into four main stages. First stage is the preliminary study on the effect of the masterbatch technique on the basic properties of unsaturated polyester. Masterbatch technique is the mixing of powder P84 Polyimide with liquid MEKP prior to be incorporated into the polyester resin, where a mixture that contain both filler and curing agent was produced. This mixture were prepared in bulk, stored in a closed container and only taken out when needed. The results showed that the masterbatch technique does not affect the gel time but does increased the Tg. The second stage was the preparation of the matrixfilled system as a function of different preparation techniques where two matrix systems were studied. First was the unsaturated polyester filled with masterbatch P84 Polyimide system and the second was the unsaturated polyester filled with P84 Polyimide system. The difference between the systems was the preparation technique. The first system was prepared by incorporating both filler and curing agent (masterbatch P84 Polyimide) simultaneously into the polyester resin...